INTERSECTIONS BETWEEN THEORETICAL-POLITICAL AND METHODOLOGY OF LABOR STUDIES: A DIALOGUE AMONG, LABOUR SOCIOLOGY, HISTORY OF SOCIAL WORK AND LABOUR GEOGRAPHY - Perpetua, Guilherme Marini [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2016)
Recent changes in world of labor have overcome the intrinsic limits to the different currents dedicated to the study of work and the working class. In the center of the current debate are the social subjects that work in different ways, as much in the use of theoretical and methodological instruments, as in the political and ideological differences, both inseparable. From the dialogue between the knowledge produced in three different disciplines (Sociology of Labor, the Social Labor History and Labor Geography), the present article aims to indicate theoretical-methodological and political issues that, in our view, have contributed to obscure, even more, the reality of work and workers, and on the other hand, enhance the analysis and contribute to the struggles of workers.
Keywords: world of labor; philosophical method; search methodologies